(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Thin films of PdCdS ternary compound have been successfully deposited using chemical baths containing cadmium acetate, lead acetate thiourea and ammonia. The films were characterised using a variety of techniques. X-ray diffraction analysis revealed that a number of prominent high intensity diffraction peaks originating from reflections of the tetragonal lead sulphide structure. Several smaller low intensity peaks related to reflections of the hexagonal structure of cadmium sulphide, were also observed. Scanning electron microscopy showed a compact layer with a surface composed of platelike shaped nanocrystals of different dimensions with well defined boundaries. Energy dispersive X-ray spectroscopy confirmed the presence of lead cadmium and sulphide. The band gap determined from optical absorption spectroscopy was found to be 1.9 eV.